PROGRAM LITERASI MEMBACA DI ISBANBAN SEBAGAI IMPLEMENTASI PROYEK KEPEMIMPINAN II PPG PRAJABATAN UNIVERSITAS SULTAN AGENG TIRTAYASA - Shafira, Irfiani; Avivi, Ami Aviatin; Salamah, Anisa Umu; Avianti, Maulida Nur; Jamaludin, Ujang; Saefullah, Asep (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
The literacy program is part of the government's program to improve the quality of Indonesian human resources. The results of the preliminary study show that there is still a lack of facilities to support reading literacy activities at partner locations, namely ISBANBAN. The purpose of this service is to assist in increasing the quantity and quality of reading literacy support facilities, as an implementation of the Untirta PPG Leadership II project. Another goal of this service is to increase children's interest in reading through various reading literacy activities. The method used in this community service activity is through community education activities, namely assisting children in reading literacy activities. The result of this service activity is an increase in reading literacy facilities, such as: procurement of reading books, provision of literacy corners, ideal trees, and professional literacy activities. In addition, the results of this dedication show an increase in children's interest in reading.